Efektifitas Konseling Rasional Emotif Behavioral untuk Meningkatkan Resiliensi Pasien Pasca Operasi Kanker di RSUD Al-Ihsan Provinsi Jawa Barat - Rahayu, Hayinah (Jurnal Bimbingan dan Konseling Islam, 2019)
This study aims to examine the effectiveness of rational emotive behavioral counseling in improving 3 aspects of resilience, namely aspects of I have, I am, and I can in patients after cancer surgery at Al-Ihsan Regional Hospital. The study was conducted at the Al-Ihsan Regional General Hospital with a subject of 21 post-cancer surgery patients using a random sampling technique. The study uses a quantitative approach with the method of equivalent control group design and data analysis using statistical analysis of percentages and One way ANOVA. This study uses 3 types of resilience instruments (I have, I am, and I can) using a Likert scale. The results showed rational emotive behavioral counseling interventions tested effective for increasing patient resilience